Incidence and predictors of frailty progression among octogenarians with ST-elevation myocardial infarction undergoing primary percutaneous coronary intervention. (September 2022) - Tashiro, Hiroshi; Tanaka, Akihito; Takagi, Kensuke; Uemura, Yusuke; Inoue, Yosuke; Umemoto, Norio; Negishi, Yosuke; Shibata, Naoki; Yoshioka, Naoki; Shimizu, Kiyokazu; Morishima, Itsuro; Watarai, Masato; et al.
Highlights: In-hospital frailty progression was commonly observed in octogenarians with STEMI. Patients with frailty progression had more severe conditions. Patients with frailty progression had more complications and longer hospital stays. Age and Killip 4 status were significant predictors of frailty progression. Abstract: Background: Frailty is one of the most serious health problems in older individuals with cardiovascular disease. Moreover, frailty progression is associated with subsequent adverse outcomes; therefore, the prevention of frailty progression is an important clinical issue. However, the incidence and predictors of frailty progression following acute myocardial infarction have not yet been fully elucidated. Methods: The present study is a sub-analysis of an observational multicenter registry retrospectively evaluating clinical outcomes of 288 octogenarians who underwent primary percutaneous coronary intervention (PCI) for ST-elevation myocardial infarction (STEMI) between January 2014 and December 2016 at five hospitals. We identified 244 patients who survived until discharge and evaluated frailty at baseline and discharge using the Clinical Frailty Scale (CFS). We defined frailty progression as an increase of at least one level in the CFS score at discharge from baseline and assessed the predictors of frailty progression. Results: Frailty progression was observed in 29.5% of patients. Patients with frailty progression were older, had more severe conditions with a higher prevalence of Killip 4 status and mechanical circulatory support use, more frequently experienced in-hospital events such as stroke (4/72, 6% vs. 0/172, 0%, p = 0.007), and had longer hospital stays than those without frailty progression [19 (11–35) vs. 13 (9–19) days, p <0.01]. Multivariate analysis showed that age (odds ratio 1.08, 95% confidence interval 1.00–1.17, p = 0.046) and Killip 4 status at baseline (odds ratio 3.34, 95% confidence interval 1.26–8.85, p = 0.01) were significant predictors of frailty progression. Conclusions: In-hospital frailty progression was commonly observed in octogenarians with STEMI who underwent primary PCI and survived until discharge, and was associated with more severe clinical conditions.